Ensayos internacionales de rendimiento de frijol para monocultivo - Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1979)
CIAT is currently the world center for all the germplasm of the genus Phaseolus. The bean program has the main objective of increasing bean production and productivity. Germplasm improvement involves a program of evaluation and identification of genetic diversity, improvement through more effective methods, trials on exptl. lines and advanced selections under a wide range of ecological conditions. Var. stability and adaptation, and the elimination of factors that advasely affect production such as diseases, insects and drought is sought along with the increase in the plant yield potential. The identification process of promising lines begins at the Bean Team Nursery (VEF) where material is evaluated according to the former aspects and afterwards, the best selections are passed on to a preliminary yield trial (EP) where they are evaluated for yield, disease- and pest-resistance of minor importance, tolerance to drought, low levels of P and resistance to high temp. EP trials are conducted in 2 regions of Colombia (Palmira and Popayan) and ue later sent to the International Bean Yield and Adaptation Nursery (IBYAN). Material forming the IBYAN is grouped in 3 categories: (1) material resulting from EP (lines from CIATs bean program, var. from the germplasm bank and lines or var. sent by national programs); (2) material chosen by the coordinator of the trial, and (3) national, international and elite controls, that are high-yielding plants showing desirable characteristics. An explanation is given on how exptl. trials are conducted, the analysis and evaluation of IBYAN results for the obtainment of promissory lines and var. Tables are presented on the characteristics of commercial var. and var. requirements for main production areas. (CIAT)